Incidence of emergency department presentations for traumatic brain injury in Indigenous and non-Indigenous residents aged 15-64 over the 9-year period 2007-2015 in North Queensland, Australia - Adrian Esterman; Fintan Thompson; Michelle Fitts; John Gilroy; Jennifer Fleming; Paul Maruff; Alan Clough; India Bohanna (BMC, 2018)
Abstract Background Traumatic brain injury (TBI) is a leading cause of disability worldwide. Previous studies have shown that males have a higher incidence than females, and Indigenous populations have a higher rate than non-Indigenous. To date, no study has compared the incidence rate of TBI between Indigenous and non-Indigenous Australians for any cause. Here we add to this rather sparse literature. Methods Retrospective analysis of data from North Queensland Emergency Departments between 2007 and 2015 using Australian Bureau of Statistics population estimates for North Queensland residents aged 15-64 years as denominator data. Outcome measures include incidence rate ratios (IRR) for TBI presentations by Indigenous status, age, sex, year of presentation, remoteness, and socio-economic indicator. Results Overall incidence of TBI presentations per 100,000 population was 97.8. Indigenous people had an incidence of 166.4 compared to an incidence in the non-Indigenous population of 86.3, providing an IRR of 1.93 (95% CI 1.77-2.10; p < 0.001). Males were 2.29 (95% CI 2.12-2.48; p < 0.001) times more likely to present than females. Incidence increased with year of presentation only in the Indigenous male population. Conclusions The greater burden of ED presentations for TBI in the Indigenous compared with the non-Indigenous population is of concern. Importantly, the need to provide quality services and support to people living with TBI in remote and very remote areas, and the major role of the new National Disability Insurance Scheme is discussed.